Pengembangan E-Modul Agrofisika Untuk Mendukung Pertanian Industrial Berkelanjutan - Anggraeni, Firdha Kusuma Ayu; Prihandono, Trapsilo; Sudarti, Sudarti; Harijanto, Alex; Arimurti, Dyah Arum; Baihaqi, Habibah Khusna; Kariimah, Niswatul; Fadilah, Tyas Nisa (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop an Agrophysics e-module using the Articulate Storyline application and to evaluate its validity and feasibility as a teaching material to support sustainable industrial agriculture. A research and development method based on the 4D model was employed, encompassing the define, design, and develop stages. The research instruments included material and media expert validation sheets as well as user response questionnaires. Validation was conducted by three experts, and user trial responses were collected from 28 students. The data were analyzed using descriptive statistical techniques. The results of the material expert validation yielded an average score of 3.63, categorized as highly feasible, while media validation produced an average score of 3.33, also classified as highly feasible. Preliminary trial results indicated user responses with an average score of 3.70, falling within the highly feasible category. Consequently, the Agrophysics e-module was deemed feasible for use as a teaching material. The module was designed to integrate recent developments in the application of physics concepts in agriculture. Therefore, the developed e-module contributes to multidisciplinary physics learning within the context of supporting sustainable industrial agriculture.